Selected salivary antioxidants and gingival health condition among a group of obese females aged 20-22 years in Baghdad, Iraq (Mustansiria Dental Journal, 2019)
Background: Obesity and periodontal disease are diseases of multifactorial etiologyclosely related to dietary habits and sociodemographic background of theindividuals. The aim of this study was the assessment of selected salivaryantioxidants and gingival health condition among a group of obese females aged20-22 years in comparison with normal weight females.Materials and methods: The study group included 40 obese females, with an agerange 20-22 years old. The control group included 40 normal weight females ofthe same age. Body weight was assessed by using the Body Mass Index (BMI).Collection of unstimulated salivary samples was carried out under standardizedconditions. Plaque and gingival indices were used for recording the oral hygieneand gingivitis. Salivary flow rate was measured then salivary samples wereanalyzed to determine the concentration of salivary antioxidants (total protein anduric acid).Results: The data analysis of the present study found that the level of salivary totalprotein was lower among the obese females compared to the normal weightfemales with statistically highly significant difference (p